Malnutrition and Muscle Loss Mediate the Association Between NT-proBNP and Mortality in Hospitalized Older Adults - Tao J; Zhang X; Wang N; Cheng D (Clinical Interventions in Aging)
Jun Tao,1,2 Xiaoyan Zhang,2 Niansong Wang,1 Dongsheng Cheng1 1Department of Nephrology, Shanghai Sixth People’s Hospital Affiliated to Shanghai JiaoTong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Geriatrics, Shanghai Sixth People’s Hospital Affiliated to Shanghai JiaoTong University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Dongsheng Cheng, Department of Nephrology, Shanghai Sixth People’s Hospital Affiliated to Shanghai JiaoTong University School of Medicine, No. 600, Yi Shan Road, Shanghai, 200233, People’s Republic of China, Tel +86-021-64369181, Email 191284172@qq.com Niansong Wang, Department of Nephrology, Shanghai Sixth People’s Hospital Affiliated to Shanghai JiaoTong University School of Medicine, No. 600, Yi Shan Road, Shanghai, 200233, People’s Republic of China, Tel +86-021-64369181, Email wangniansong2012@163.comBackground & Aims: Elevated N-terminal pro-B-type natriuretic peptide (NT-proBNP), a biomarker of cardiac stress, predicts mortality in heart failure. Its association with outcomes in older hospitalized patients without overt heart failure, and potential mediation by malnutrition and muscle loss, remains unclear. The purpose of this study was to assess the association between NT-proBNP and mortality in hospitalized oldest-old adults (≥ 80 years) and to explore the mediating role of malnutrition and muscle loss.Methods: This prospective cohort study was conducted among 360 hospitalized patients ≥ 80 years of age (median age 87 years, 24.4% women) in the Department of Geriatrics (Shanghai, China), between August 2017 and January 2018. The Geriatric Nutritional Risk Index (GNRI) and Mini Nutritional Assessment Short Form (MNA-SF) were used for nutritional assessment, while calf circumference was used as a measure of muscle mass. A Cox proportional hazard model was used to assess the relationship between NT-proBNP levels and mortality. Mediation analysis was used to explore the mediating effects of malnutrition and muscle loss.Results: The median follow-up was 4.1 years with 159 (44.1%) deaths. Mortality risk increased by 32% per 2-fold increase in NT-proBNP levels (full adjusted hazard ratio: 1.32 [95% Confidence Interval (CI), 1.20– 1.46]). A mediation analysis showed that a lower GNRI score and decreased calf circumference partially mediated the effects of high NT-proBNP and mortality risk, with an estimated relative effect size of 28.9%, while MNA-SF and calf circumference mediated with an estimated relative effect size of 25.3%.Conclusion: NT-proBNP levels were associated with increased mortality in hospitalized older patients. Moreover, the detrimental effects of NT-proBNP on survival were partly mediated by malnutrition and muscle loss. Consequently, preventive and nutritional strategies should be required for these patients.Plain Language Summary: Hospitalization poses greater risks with aging. Research shows elevated NT-proBNP—a cardiac biomarker—predicts higher mortality in hospitalized older adults. Assessments revealed increased mortality risk with rising NT-proBNP levels, significantly mediated by malnutrition and muscle loss. These findings indicate NT-proBNP reflects broader physiological decline, highlighting the critical need to evaluate nutritional and muscle status. Screening enables targeted interventions like dietary support and physical activity to improve outcomes.Keywords: natriuretic peptide, sarcopenia, malnutrition, hospitalization, oldest-old